Hungarian mathematicians in the twentieth century: Ottó Varga (1909–1969) - Kántor, Tünde (Teaching Mathematics and Computer Science, 2010)
In this article we want to present life and work of Ottó Varga on occasion of the centenary of his birth. He was an outstanding geometer, the head of the Mathematical Seminar / Department (1942-1959) and the first dean of the Faculty of Sciences of the University of Debrecen (Hungary).His area of research was differential geometry. The Debrecen school of differential geometry emerged due his activity. He wrote 57 papers.